Disparities Influencing Functional Outcomes Between Rural and Urban Patients With Acute Stroke - Llanos-Leyton, Natalia; Pardo, Carlos; Pinilla-Monsalve, Gabriel D.; Arango, Akemi; Valderrama, Jaime; Pugliese, Isabella; Amaya, Pablo (Frontiers in Neurology, 2022)
Introduction:There is scarce information in Latin America about factors related to stroke patient outcomes in rural areas compared with urban areas. Objective:To evaluate the functional outcomes of stroke code patients from rural and urban areas and their relationship with socioeconomic disparity. Methods:This observational, analytical, and prospective cohort study included patients of urban, semiurban, and rural origin with stroke codes from a university hospital in southwestern Colombia between 2018 and 2019. Demographic and clinical data and modified Rankin at discharge and at the 3-month follow-up were analyzed. The poverty index, barriers to health access and availability of ambulances by the municipality were assessed at an ecological level. Results:555 stroke patients were registered;21.2% from rural areas, 432 (77.98%) had an ischemic stroke. There were no significant differences in sociodemographic factors or medical background. Urban patients had lower rates of reperfusion therapy (23.25%). Favorable mRS at discharge (<3) was higher in urban areas (63.03%), and mortality was higher in rural patients (13.56%). The ambulance rate in semiurban and rural areas was as low as 0.03 per 100.000 inhabitants, and the poverty index was 11.9% in urban areas vs. 23.3% in semiurban and rural areas. Conclusions:In municipalities with the lowest ratio of ambulances per 100,000 inhabitants, an increase in Rankin score at discharge is more significant. There is an inverse relationship, which is not related to the poverty rate or the percentage of people with barriers to access to health. There is a need for further studies that assess barriers inherent in rural patients.